SOLID WASTE MANAGEMENT PRACTICES IN SUDERBANI TOWN OF RAJOURI DISTRICT - Darshni, Priya; Jamwal, Annie (International Journal of Psychosocial Rehabilitation, 2020)
The Resource Conservation and Recovery Act (RCRA) 1976, which forms the basis of waste management programs in America defines solid waste as any garbage or refuse, sludge from a wastewater treatment plant, water supply treatment plant, or air pollution control facility and other discarded material, resulting from industrial, commercial, mining, and agricultural operations, and from community activities (UN Environmental Protection Agency). In India, management of such waste product is the domain of urban and rural local bodies. These bodies regulate the process of waste disposal from its inception to final disposal. However, there are many limiting factors that play a major role in making this whole process a challenging one. At municipal level solid or semi-solid domestic waste involves sanitary waste, commercial waste, institutional waste, catering and market waste and other non-residential wastes, street sweepings, silt removed or collected from the surface drains, horticulture waste, agriculture and dairy waste, treated bio-medical waste excluding industrial waste, biomedical waste and e-waste, battery waste, radio-active waste generated in the area under the local authorities and other entities (SWM Rules, 2016).This papers aims to analyse various kinds of wastes generated in town of Sunderbani in Rajouri district and the issues involved with the disposal of such wastes.